Baroque ways of seeing - Cavanna, Pierangelo (Abaton. Revista de figuración, representación e imágenes de la arquitectura, 2023)
The photographic documentation of the Baroque architectures, considered here in some Piedmontese examples, went with the growth of their critical fortune. It has also represented a fruitful opportunity to verify the very narrative modalities of photography, witnessing the passage from the descriptive intention proper to nineteenth-century culture, and from the modernist formalizations then, to a more fully interpretative will, where photography turns out to be an instrument of critical reading, the more effective the more adherent to the logic of Baroque visuality, up to risk a photographic reinvention of those same architectures.
Keywords: Architectural photography; Baroque; Gallo; Francesco; Guarini; Guarino; Juvarra; Filippo; Piedmont; Vittone; Bernardo Antonio